Criminalization of Cohabitation in the New Criminal Code (A Philosophical Review in Legal Pluralism and Privacy Rights) - Cahyo Dimasre Bimantoro; Rangga Jayanuarto; Fahmi Arisandi; Hendri Padmi (International Journal of Social Sciences and Humanities, 2026)
The criminalization of cohabitation under Article 412 of Law No. 1 of 2023 on the Criminal Code has sparked debate over the legitimacy of government interference in individuals' private domains. This study aims to analyze the philosophical basis of criminalizing cohabitation through the perspectives of legal pluralism and privacy rights, assess its proportionality within a democratic constitutional order, and explain the legal and sociological consequences of implementing this article. This research is a normative legal study with a qualitative, descriptive-analytical approach, utilizing normative and philosophical legal methods by examining primary, secondary, and tertiary legal materials. The results indicate that criminalizing cohabitation does not meet the principles of proportionality and harm in modern criminal law, because consensual relationships between two adults do not cause concrete harm to third parties. Furthermore, it violates privacy rights protected under Article 28G (1) of the 1945 Constitution and Article 17 of the ICCPR, and creates tension within Indonesia's pluralistic legal landscape. The application of this article has the potential to trigger overcriminalization and social stigmatization, thus requiring a reinterpretation of the complaint offense and the prioritization of the principle of ultimum remedium to maintain a balance between public morality norms and individual human rights guarantees within a democratic rule of law framework.